Promote Innovation In Madrasah Through The Use Of Educational Technology - Andri Sungkowo; Aris Susanto; Arifannisa; Axelon S Renyaan; Erna Widyasari (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2024)
The research aims to explore and evaluate the application of educational technology in promoting learning innovation in the madrasah. With the increasing importance of technology integration in the world of education, madrasas also need to adapt teaching methods by integrating relevant digital tools and resources. The research digs into a range of strategies that can be applied by the matrasah to integrate educational technology effectively, including teacher training, developing technological infrastructure, revising curricula, and applying project-based learning using technology. The study uses a qualitative approach through literary research methods, by reviewing and analyzing previous studies, reports, and data on similar topics. Research results show that the use of educational technology in the madrasah has significant potential to drive innovation in the teaching learning process. The training and professional development of teachers is identified as a key factor in the successful implementation of technology, with adequate technological infrastructure as an essential prerequisite. The integration of curricula with digital resources and the implementation of technology-supported project-based learning strategies has proven to enhance student engagement and deepen their understanding of the subject matter. However, challenges such as limited access to technological resources, lack of effective teacher training, and resistance to change in traditional learning practices are also identified as obstacles to be overcome.